Analisis Implementasi Kebijakan Fasilitas Pembebasan Pajak Untuk Jangka Waktu Tertentu (Tax Holiday) Dalam Meningkatkan Investasi Di Indonesia Tahun 2018 - Enggal Rahayu Dwi Handoyo; Tri Djoko Hardjono (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Investment is one source for the government to increase state revenue. To attract investors' attention, the government provided tax exemption facilities known as Tax Holiday. The Indonesian government has issued a policy of providing a facility in the form of Tax Holiday through PMK 150 of 2018 which regulates the provision of corporate income tax deduction facilities, especially for pioneer industries. The purpose of this study was to analyze the implementation of the Tax Holiday policy, the obstacles of the implementation and how to overcome these obstacles. The analytical method used was descriptive qualitative. The results of this study showed that the implementation of the Tax Holiday policy had been carried out well, but it was not optimized in its implementation, and there were still very few of investors who wanted to invest in Indonesia. This was caused by the still lack of socialization carried out for the policy, resulting in the not successful implementation of the Tax Holiday policy. From the results of the study, it is expected that BKPM and DGT to be more active and increase their socialization activities so that the implementation of this Tax Holiday policy will be successful and can reach the expected targets.